Intravenous high‐dose interferon with or without maintenance treatment in melanoma at high risk of recurrence: meta‐analysis of three trials. (8th December 2015) - Malczewski, Agnieszka; Marshall, Andrea; Payne, Miranda J.; Mao, Lili; Bafaloukos, Dimitrios; Si, Lu; Pectasides, Dimitrios; Fountzilas, George; Guo, Jun; Gogas, Helen; Middleton, Mark R.
Abstract: Resected stage IIB–IIIC malignant melanoma has a poor prognosis with a high risk of relapse and death. Treatment with adjuvant interferon alfa‐2b (IFN‐ α ‐2b) is associated with improved relapse‐free and overall survivals (OS), but the most appropriate dose and duration of treatment are unknown. In this article, we present an individual patient data random effects meta‐analysis of melanoma patients from the U.K., Greek, and Chinese randomized trials. All patients were randomized either to IFN‐ α ‐2b 15–20 MIU/m 2 IV daily 5 days per week for 4 weeks (IV) or to the same regimen followed by IFN‐ α ‐2b 9–10 MIU/m 2 administered three times per week for 48 weeks (IV and SC). Allowing for dose interruptions and reductions, an equivalent total dose of IFN‐ α ‐2b was delivered in all three studies. We assessed whether IV was noninferior to IV and SC in terms of relapse‐free survival (RFS) and investigated tumor and patient characteristics that impacted on outcomes. Median follow‐up of 716 stage IIB–IIIC patients was 5.4 years. Noninferiority of IV compared to IV and SC could not be conferred for RFS (hazard ratio [HR] 1.16, 95% confidence interval [CI] 0.89–1.52; noninferior P  = 0.17). Stage ( P  < 0.0001), site (acral vs. other, P  < 0.0001), and Breslow thickness ( P  = 0.02) were significant predictors of RFS. The HR for death was 1.13 for IV compared to IV and SC, (95% CI 0.91–1.39). Stage ( P  < 0.0001) and Breslow thickness ( P  = 0.001) were significant independent predictors of OS. The available data suggest that where adjuvant high‐dose interferon is being considered there is no evidence to deviate from the year long regimen described in the Eastern Cooperative Oncology Group and Intergroup studies. Abstract : Interferon delays and melanoma relapse can be prevented, but at the cost of significant toxicity. We analyzed three trials to see if a shorter regimen might be able to replace the favored yearly course. We found no evidence to support a change in regimen.